Dynamic modeling for optimal subsurface reservoir fluid mapping in Mature oil fields - Hamada, Ghareb M.; Dahab, Abdel Sattar M.; Salim, Mahmoud M. (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
Development of a mature oil reservoir blocks strategy in optimizing hydrocarbon production from mature oil fields. Using dynamic modeling techniques together with subsurface interpretations that were based on sharply adjacent well data, the study has presented new development well placements. Production data studies, pressure surveys, and detailed subsurface studies will be integrated to improve the understanding of the reservoir behavior to predict reservoir performance. The key findings indicate high increments in oil production on account of the implementation of new development wells. The current research provides not only empirical evidence supporting the efficacy of strategic drilling but also lends a structured workflow applicable for similar mature oil fields, thus providing practical means for increasing production and improvement in field life. Opportunities that deliver high value yet have limited associated risks and costs are typically characterized in general by short payout periods and reinvestment of savings. Unlocking residual potential from low-productivity or shut-in wells, maximizing asset value, and using information to drive decisions on optimizing is an asset development strategy. These strategies can only be effectively implemented if inter-disciplinary teams work together to ensure that data is comprehensively analyzed and all solutions are formulated in line with these analyses.   This work discusses the efficiency of developing non non-drained oil reservoir blocks strategy in optimizing hydrocarbon production from mature oil fields. Using dynamic modeling techniques together with subsurface interpretations that were based on sharply adjacent well data, the study has presented new development well placements. The study of the Abu Rudeis oil field has laid the foundation for long-term optimization, integrating production data, pressure surveys, and geological studies into a comprehensive reservoir management strategy. The interdisciplinary approach ensured well-informed and targeted decisions, resulting in enhanced hydrocarbon recovery and improved field performance. Results from the three-dimensional grid that captured heterogeneity in the reservoir, the assignment of reservoir properties like porosity and permeability, and fluids distribution helped to leverage data-driven strategies and advanced technology, the field's sustainability and efficiency have been significantly improved, providing a strong foundation for future optimization efforts.